Réponses

2014-05-25T19:46:40+02:00
1)
5x + 6 - 18 = 3x + 4
5x - 3x = 4 - 6 + 18
2x = 16
x = 16/2
x = 8

2)
4 + 17 - 5x = 7x + 6
- 5x - 7x = 6 - 17 - 4
- 12x = -15
x = 15/12

3)
25 - 52x + 3 = x
- 52x - x = - 3 - 25
- 53x = - 28
x = 28/53

4)
28 + 9x - 6 = 2x + 3
9x - 2x = 3 - 28 + 6
7x = - 19
x = - 19/7

5)
22 + 3x - 6 = 0
3x = - 22 + 6
3x = - 16
x = - 16/3

6)
48 + 2x - 26 = 39x + 2
2x - 39x = 2 + 26 - 48
- 37x = - 20
x = 20/37

7)
75 - 3x + 2x = 8
- 3x + 2x = 8 - 75
-x = - 67
x = 67

8)
2x + 5x = 8 - 6
7x = - 2
x = - 2/7

9)
32x - 8 + 14x = 0
32x + 14x = 8
46x = 8
x = 8/46
x = 4/23

10)
55x + 63 - 4x = 22
55x - 4x = 22 - 63
51x = - 41
x = - 41/51

11)
9 + 2x + 7 = 0
2x = - 7 - 9
2x = - 16
x = - 16/2
x = - 8

12)
23 + 14x + 65x = 74 - 2
14x + 65x = 72
79x = 72
x = 72/79

13)
15 - 42x + 54x - 63 = 0
 - 42x + 54x =  63 - 15
12x = 48
x = 48/12
x =4

14)
21x + 6x = 9x + 23
21x + 6x - 9x = 23
18x = 23
x = 23/18

15)
9 + 2x - 16 =  - 9x
2x + 9x = 16 - 9
11x = 7
x = 7/11

16)
3x + 78 - 25 = - 6x
3x + 6x = 25 - 78
9x = - 53
x = - 53/9

17)
14x - 23 - 5x = 0
14x - 5x = 23
11x = 23
x = 23/11

18)
47x + 6x - 5 = 7x + 18 - 9
47x + 6x - 7x = 18 - 9 + 5
46x = 14

19)
96x - 54x = 18 + 19
42x = 37
x = 37/42

20)
25 + 3x - 9x = 32
3x - 9x = 32 - 25
- 6x = 7
x = - 7/6

21)
- 65 + 42x + 3x = 0
42x + 3x = 65
45x = 65
x = 65/45
x = 13/9

22)
4x + 5 = 2x - 4
4x - 2x = - 4 - 5
2x = - 9
x = - 9/2

23)
4x + 10 = 3x + 12
4x - 3x = 12 - 10
x = 2

24)
x/2 + x + 3 + x + 5 = 0
           4
2x/4 + x + 3 + 4x + 20 = 0
             4            4
7x + 23 = 0
     4
7x + 23 = 0
7x = - 23
x = - 23/7

25)
2x + 5 = 13  - x
2x + x = 13 - 5
3x = 8
x = 8/3

26)
27x - 31x = 101 + 471
- 4x = 572
x = - 572/4
x = - 143

27)
21x + 5 - 18 = - 3x
21x + 3x = - 5 + 18
24x = 13
x = 13/24

28)
14 - 25x + 65x = 2 - 3
- 25x + 65x = 2 - 3 - 14
40x = - 15
x = - 15/40

29)
47 + 3x - 8 = - 15x
3x + 15x = - 47 + 8
18x = - 39
x = - 39/18
x = - 13/6

30)
21x + 2x = x + 65
21x + 2x - x = 65
22x = 65
x = 65/22